1988
DOI: 10.1161/01.hyp.12.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstriction and hypersensitivity to vasoactive substances after acute volume expansion in dogs.

Abstract: SUMMARY In a search for factors contributing to the sustained Mood pressure (BP) elevation in acutely volume-loaded animals, dextran dissolved in lactated Ringer's solution (20 ml/kg) was infused into 34 mongrel dogs over a period of 1 hour under pentobarbital anesthesia and changes in bemodynamic and humoral variables were monitored during its infusion and for 3 hours after its infusion. BP elevation during volume loading (from 114 ± 3 to 128 ± 3 [SEM] mm Hg) was attributed to an increase in cardiac output. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In a previous study on acute volume expansion, 11 we found that all dogs showed cardiac outputdependent hypertension during volume expansion and that blood pressure 3 hours after infusion was stopped was attributed to increase in the TPR. Peripheral sympathetic activity, the reninangiotensin system, and vasopressin did not seem to contribute to this vasoconstriction, and our results provided no evidence against the systemic autoregulation theory.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In a previous study on acute volume expansion, 11 we found that all dogs showed cardiac outputdependent hypertension during volume expansion and that blood pressure 3 hours after infusion was stopped was attributed to increase in the TPR. Peripheral sympathetic activity, the reninangiotensin system, and vasopressin did not seem to contribute to this vasoconstriction, and our results provided no evidence against the systemic autoregulation theory.…”
Section: Discussionmentioning
confidence: 68%
“…This destruction of the barorefiex was confirmed by the complete lack of bradycardia during volume expansion in groups II and IV. Decrease in the TPR may be partly due to decreases in the renin-angiotensin system 11 ' 19 and vasopressin, 11 which would contribute to vascular relaxation. Decrease in viscosity resulting from decrease in the hematocrit 11 would also cause reduction of the calculated TPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volume expansion itself is an unlikely explanation for the increase in vascular responsiveness to NA (24). To correct for any change in pressor response during the clamp as a consequence of the infusion of dextrose 20% to maintain euglycemia, all subjects received corresponding amounts of water orally on the day of the control experiment.…”
Section: Discussionmentioning
confidence: 99%
“…To correct for any change in pressor response during the clamp as a consequence of the infusion of dextrose 20% to maintain euglycemia, all subjects received corresponding amounts of water orally on the day of the control experiment. Moreover, any change in cardiovascular reactivity would have been expected to affect the pressor response to NA and All equally (24). The (43,44).…”
Section: Discussionmentioning
confidence: 99%